Field Performance of Mungbean (Vigna radiata Wilczek) Seed differing in Vigour Levels. - Mohd. Lassim, Mohammad B.; Thong, Faa Chee (1981)
A study was conducted at Universiti Pertanian Malaysia, Serdang, Selangor, to investigate the influence of seed vigour on field performance of Vigna radiata. Seeds of the U-Thong cultivar of medium and low vigour were obtained by subjecting high quality seeds to an atmosphere of high temperature and high relative humidity. Genninability of seeds cOrresponded directly with their respective vigour' levels, with the differences being significant. Some yield component characteristics were found to be significantly influenced by seed vigour. Plants established from high vigour seeds produced significantly higher seed yield (1300 kg/ha) than those from medium (884 kg/ha) and low vigour seeds (767 kg/ha). However, some vegetative characteristics did not appear to be influenced by seed vigoUl·.